IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM KURIKULUM MERDEKA DI SD NEGERI SINGKUP - APIP MUHAMMAD RIZKI APIP; Eliya Rochmah; Nurkholis (EDUTARY (Education of Elementary School), 2024)
The Pancasila Student Profile Strengthening Project is project-based co-curricular learning carried out outside of intracurricular learning hours to strengthen competencies or character according to the dimensions of the Pancasila student profile. Singkup State Elementary School is one of the schools that has implemented the Merdeka Curriculum in July in grades I and IV and has carried out project activities to strengthen the profile of Pancasila students. This research aims to find out how the project to strengthen the profile of Pancasila students in the Merdeka Curriculum in class 1 of Singkup State Elementary School is implemented. The type of research used by the author is descriptive qualitative field research, namely observation, interviews and documentation. The data analysis technique uses the method developed by Miles and Huberman, namely reducing data, presenting data, and verifying data. The results of this research show that there are 1). project planning by creating a coordination team, identifying the level of school readiness, determining dimensions, themes, and time allocation, compiling project modules, and creating a reporting strategy for project activities. 2). implementation of project activities, starting with the preparation stage such as coordination with the school principal, activity preparation meetings with colleagues, socialization of activities with parents and students, making monitoring and evaluation instruments, and preparing tools and materials, then the implementation stage begins with getting to know yourself, organizing groups, paper, making handicrafts from organic/inorganic waste which is carried out for two days, and reflection. 3). Project evaluation at Singkup State Elementary School is carried out using monitoring instruments for program implementation and evaluating the achievement of the Pancasila student profile.